Outcomes of a Bladder Cancer Screening Program Using Home Hematuria Testing and Molecular Markers - Bangma, Chris H.; Loeb, Stacy; Busstra, Martijn; Zhu, Xiaoye; El Bouazzaoui, Samira; Refos, Jeanine; Van Der Keur, Kirstin A.; Tjin, Stephen; Franken, Conja G.A.M.; van Leenders, Geert J.L.H.; Zwarthoff, Ellen C.; Roobol, Monique J. (European urology, 2013)
We previously reported the preliminary findings from a feasibility study of bladder cancer (BCa) screening with urinary molecular markers (Bladder Cancer Urine Marker Project [BLU-P]) that has now been terminated. To report the final results from BLU-P to determine whether mass screening for BCa is feasible and useful. BLU-P was a Dutch population-based study initiated in 2008 to evaluate BCa screening. A total of 6500 men were invited to participate in the study, 1984 (30.5%) agreed, and 1747 (88.1%) men completed the protocol and were followed for 2 yr. The screening protocol included home hematuria testing followed by molecular markers—nuclear matrix protein 22 (NMP22), microsatellite analysis (MA), fibroblast growth factor receptor 3 (FGFR3) mutation snapshot assay, and a custom methylation-specific (MLPA) test—to determine the need for cystoscopy. Outcomes included the number of cystoscopies and the cancer detection rate within and outside the protocol, as determined by linkage to national registries. Overall, 409 men (23.4%) tested positive for hematuria and underwent molecular testing. Current smokers (n=295 [17%]) and past smokers (n=998 [58%]) were significantly more likely to test positive for hematuria than nonsmokers. Seventy-one of 75 men (94.6%) with positive molecular markers underwent the recommended cystoscopy. Four BCas and one kidney tumor were detected through this sequential protocol, whereas one BCa and one kidney tumor were missed through the screening program. Limitations include the possibility of healthy subject bias. For BCa screening, use of a sequential protocol with home hematuria testing followed by molecular markers substantially reduced the number of cystoscopy recommendations compared with dipstick testing alone. A sequential screening approach may help minimize unnecessary invasive follow-up testing, with very few missed cancers. Nevertheless, this mass screening program had a very low diagnostic yield in an unselected asymptomatic European male population. Bladder cancer screening with home dipstick testing followed by confirmatory molecular markers reduced the number of cystoscopy recommendations compared to dipstick testing alone. Although very few cancers were missed, this mass screening program had a low diagnostic yield in an unselected asymptomatic European male population.